2017
DOI: 10.3390/ijerph14030311
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Sites and Addiction: Ten Lessons Learned

Abstract: Online social networking sites (SNSs) have gained increasing popularity in the last decade, with individuals engaging in SNSs to connect with others who share similar interests. The perceived need to be online may result in compulsive use of SNSs, which in extreme cases may result in symptoms and consequences traditionally associated with substance-related addictions. In order to present new insights into online social networking and addiction, in this paper, 10 lessons learned concerning online social network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
669
4
87

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 861 publications
(774 citation statements)
references
References 65 publications
(99 reference statements)
14
669
4
87
Order By: Relevance
“…In a recent review about the studies of SNSs addiction, it has been suggested that smartphone addiction may be a part of SNS addiction [43]. We did not explore the smartphone addiction but we analysed the effects of "using FB via smartphone" on FB overuse and addiction and we could not find a significant association between these variables.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a recent review about the studies of SNSs addiction, it has been suggested that smartphone addiction may be a part of SNS addiction [43]. We did not explore the smartphone addiction but we analysed the effects of "using FB via smartphone" on FB overuse and addiction and we could not find a significant association between these variables.…”
Section: Discussionmentioning
confidence: 78%
“…For example, nicotine and alcohol use are positively associated with self-reported impulsivity symptoms [41] and increases in the number of impulsivity and conduct disorder (CD) symptoms are also associated with increased risk of other substance use disorders (SUDs) too [42]. There seems to be a similar pattern for Internet and SNSs addictions [43]. Recent studies demonstrated that impulsivity symptoms are associated with Internet addiction symptoms among children and college students with ADHD [44][45][46] and attention Table 6.…”
Section: Discussionmentioning
confidence: 80%
“…Considering the findings above, the increasing use of SNSs and the need to check the information on the mobile screen can be considered as a predictor of smartphone addiction. Smartphone addiction and Social Networking Addiction may be intertwined concepts, a notion also pronounced by Kuss and Griffiths (2017). The current study examines the relationship between smartphone addiction and factors such as age, sleep duration, SNSs use and FoMO in high school students.…”
Section: Smartphone Addiction Fomo and Sns Usementioning
confidence: 98%
“…In the recent years, it has been seen that smartphone usage has spread rapidly, having all but abolished the obligation for desktop and laptop computers due to mobile devices' ability to access the Internet and social networks with any physical or time-bound restraints. In this respect, some researchers suggest that smartphone addiction is actually part of society's dependence on social networks (Kuss & Griffiths, 2017) and that smartphone addiction is simply excessive and problematic use of social networking (Doğan & Tosun, 2016). Future studies could therefore investigate the relationship between smartphone addiction and social networking addiction.…”
Section: Is There a Relationship Between Smartphone Addiction And Stumentioning
confidence: 99%
“…Turkle describes it as "alone together": always connected via technology, but in fact isolated [10]. Despite that social networking can arguably be considered a way of being and relating than referring to what we do [11]. Social networking meets basic human needs such as needs of safety, association, estimation, and self-realization by offering the possibilities of social support and self-expression [12].…”
Section: Res Med Eng Scimentioning
confidence: 99%